Single-incision laparoscopic surgery for colorectal cancer - Hirano, Yasumitsu (World J Gastrointest Surg, 2016)
AIM: To determine the effect of single-incision laparoscopic colectomy (SILC) for colorectal cancer on short-term clinical and oncological outcomes by comparison with multiport conventional laparoscopic colectomy (CLC). METHODS: A systematic review was performed using MEDLINE for the time period of 2008 to December 2014 to retrieve all relevant literature. The search terms were “laparoscopy”, “single incision”, “single port”, “single site”, “SILS”, “LESS” and “colorectal cancer”. Publications were included if they were randomized controlled trials, case-matched controlled studies, or comparative studies, in which patients underwent single-incision (SILS or LESS) laparoscopic colorectal surgery. Studies were excluded if they were non-comparative, or not including surgery involving the colon or rectum. A total of 15 studies with 589 patients who underwent SILC for colorectal cancer were selected. RESULTS: No significant differences between the groups were noted in terms of mortality or morbidity. The benefit of the SILC approach included reduction in conversion rate to laparotomy, but there were no significant differences in other short-term clinical outcomes between the groups. Satisfactory oncological surgical quality was also demonstrated for SILC for the treatment of colorectal cancer with a similar average lymph node harvest and proximal and distal resection margin length as multiport CLC. CONCLUSION: SILC can be performed safely with similar short-term clinical and oncological outcomes as multiport CLC.